2002
DOI: 10.1590/s0074-02762002000600003
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C and hepatitis B virus infection in different hemodialysis units in Belo Horizonte, Minas Gerais, Brazil

Abstract: The prevalence, virological and epidemilogical aspects of the hepatitis C virus (HCV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
49
4
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 21 publications
5
49
4
3
Order By: Relevance
“…Also, in this study, the prevalence declined to 2.4% in 2002 (data not shown). With reference to other Brazilian hemodialysis populations, HBsAg prevalence found in Central Brazil was lower than those observed in Tocantins (4%) (Souza et al 2003) and Santa Catarina (10%) in North and South regions, respectively, and also in Belo Horizonte (4.4%) (Busek et al 2002), Rio de Janeiro (11.1%) (Vanderborght et al 1995), and São Paulo (15.1%) (Cendoroglo Neto et al 1995) in Southeast of Brazil. However, these HBsAg prevalence rates were Length of time on hemodialysis < 1 year 1.0 1.0 1 a 3 years 1.1 (0.8-1.6) 0,9 (0.6-1.4) > 3 years 2.6 (1.8-3.7) 2.6 (1.7-4. higher than those found in developed countries as Switzerland (1.6%) (Ambuhl et al 2000) and the US (1%) (Finelli et al 2005).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Also, in this study, the prevalence declined to 2.4% in 2002 (data not shown). With reference to other Brazilian hemodialysis populations, HBsAg prevalence found in Central Brazil was lower than those observed in Tocantins (4%) (Souza et al 2003) and Santa Catarina (10%) in North and South regions, respectively, and also in Belo Horizonte (4.4%) (Busek et al 2002), Rio de Janeiro (11.1%) (Vanderborght et al 1995), and São Paulo (15.1%) (Cendoroglo Neto et al 1995) in Southeast of Brazil. However, these HBsAg prevalence rates were Length of time on hemodialysis < 1 year 1.0 1.0 1 a 3 years 1.1 (0.8-1.6) 0,9 (0.6-1.4) > 3 years 2.6 (1.8-3.7) 2.6 (1.7-4. higher than those found in developed countries as Switzerland (1.6%) (Ambuhl et al 2000) and the US (1%) (Finelli et al 2005).…”
mentioning
confidence: 86%
“…Many investigations have demonstrated that duration of hemodialysis treatment is strictly correlated with hepatitis B positivity, suggesting HBV nosocomial transmission (Vladutiu et al 2000, Busek et al 2002, Otedo et al 2003). In fact, our patients under treatment for more than three years had 2.6-fold (95% CI: 1.7-4.0) greater risk of HBV infection compared to subjects who had undergone less than one year.…”
mentioning
confidence: 99%
“…In contrast, there is a high prevalence of hepatotrophic viruses in the Amazon region with virological peculiarities, such as genotype F of HBV [8,9] and hepatitis D virus [10]. Many Brazilian studies, as well as international studies, describe the prevalence of hepatotrophic viruses among specific groups, such as blood donors [11], patients in hemodialysis programs [12][13][14], hemophiliacs [15], afro-descendants [16], mental disease patients [17] and hepatitis patients [18,19]. Due to a lack of studies conducted on the Brazilian northeastern semiarid region, we examined the distribution of hepatitis A (HAV), B (HBV) and C (HCV) serological markers in this population.…”
mentioning
confidence: 99%
“…In developed countries where these measures have been implemented, HBV infection declined significantly, reaching hepatitis B surface antigen (HBsAg) rates lower than 1%, as observed in the US (Alter et al 1986, Tokars et al 2002. In Brazil, investigations have shown prevalence rates ranging from 4.4% to 15.1% (Cenderoglo Neto et al 1995, Busek et al 2002, Teles et al 2002.…”
mentioning
confidence: 99%